Remodelling the personal traits to become a competent librarian in the digital age / Asmad Rizal Umar...[et al.] - Umar, Asmad Rizal; Sa'ari, Haziah; Idrus, Marlia (2012)
There has been much discussion about the competencies issues nowadays . Research regarding the influence of personal traits towards the achievement of librarian behavior and the examining of the competencies has primarily emphasized the importance of their spiritual quotient, emotional quotient, leadership, and competencies required such as attitudes, knowledge and skill. Those competencies are required in order to become successful librarian either in terms of academic or for the future. Through of all the competencies given , it is really hoped that the librarian has the ability in leading the new generation for one day . It is every employer or manager's contention that for such an organization to be successful, all its employees must exercise personal responsibility and leadership. Therefore, in order to become successful librarian, they need to train themselves from now and have such of required competencies. Since the attended respondents of this research is focused on the member of Faculty of Information Management, the researcher hope that librarian are able to provide the information to the society and be a successful information provider. Their proficiencies need to be accomplished in a successful way . Moreover, every society today needs the right information which has to be delivered on the right time and at the right places .